SAT0582 Incidence of Malignancies in Patients with Inflammatory Rheumatic Diseases and Biological Drugs: Experience from One Center in Italy. (15th July 2016) - Bartoli, F.; Bruni, C.; Tesei, G.; Denaro, V.; Nacci, F.; Antonuzzo, L.; Di Costanzo, F.; Matucci-Cerinic, M.; Fiori, G.
Abstract : Background: Over the past decade, it has been frequently suggested that the risk of cancer may be increased in patients with inflammatory rheumatic diseases treated with biologics. These drug have been considered as reducing immune surveillance. However, data from registries from different continents reported that treatment with TNF inhibitors did not increase the risk of malignancies, except for skin cancer (1). Objectives: To evaluate the incidence of malignancies in a cohort of our patients with inflammatory rheumatic diseases treated with biological drugs. Methods: The charts of 1468 patients with Rheumatoid Arthritis, Psoriatic Arthritis and Ankylosing Spondylitis treated with Adalimumab, Etanercept, Infliximab, Certolizumab, Golimumab, Tocilizumab and Abatacept followed up from 2005 to 2015 at the Department of Rheumatology, University of Florence, were reviewed. Patients who developed a cancer (excluding basal cell skin cancer) during biological therapy were identified. The incidence of malignancies in our patients was compared to the incidence of cancer in the general population in the same period, same geographic area and with same age. Results: Out of 1468 patients, 828 (56, 4%) were affected by Rheumatoid Arthritis, 290 (19.7%) by Ankylosing Spondylitis and 350 (23.9%) by Psoriatic Arthritis. Twenty-five out of 1468 patients (1.7%) (mean age 65±9 years), developed cancer: in details, we found 5 (20%) lung cancer, 5 (20%) melanoma, 2 (8%) breast cancer, 1 (4%) liposarcoma, 1 (4%) tongue cancer, 1 (4%) colo-rectal cancer, 1 (4%) liver cancer, 1 (4%) squamous cell skin cancer, 1 (4%) intestinal lymphoma, 1 (4%) myeloid leukemia, 1 (4%) endometrial cancer, 1 (4%) cervical intraepithelial neoplasia (CIN III), 1 (4%) gastric cancer, 1 (4%) bladder cancer, 1 (4%) laryngeal carcinoma and 1 (4%) follicular NHL of parotid gland. Incidence among patients resulted as follows: 2, 05% Rheumatoid Arthritis, 1, 37% Ankylosing Spondylitis and 1, 14% Psoriatic Arthritis. The percentage of cancer in patients was respectively: Etanercept 2, 31%, Adalimumab 1, 46%, Infliximab 1, 18%, Golimumab 1%, Abatacept 1%, Tocilizumab 3, 92% and Certolizumab 2, 43%. From 2005 to 2010, the incidence of malignancies (excluding basal cell skin cancer), in general population between the age of 60 and 70 years in the Florence area was 0.39%. Conclusions: Our data suggest that in patients with inflammatory rheumatic diseases treated with biological drugs, cancer is increased of 289% compared to the general population. In these patients, the risk of malignancy still remains to be verified in larger cohorts in our area with a long-term controlled registry. References: Codreanu C, Damjanov N. Safety of biologics in rheumatoid arthritis: data from randomized controlled trials and registries. Biologics. 2015 Jan 27;9:1–6. doi:10.2147/BTT.S68949. eCollection 2015. Review. Disclosure of Interest: None declared